Novel markers of kidney injury in bipolar patients on long‐term lithium treatment. (4th November 2013) - Rybakowski, Janusz K.; Abramowicz, Maria; Chłopocka‐Wozniak, Maria; Czekalski, Stanislaw
Abstract : Objectives: We assessed kidney function in long‐term lithium‐treated bipolar patients compared with age‐matched patients not taking lithium, including novel markers of kidney injury such as plasma neutrophil gelatinase‐associated lipocalin (NGAL) and urinary beta‐2 microglobulin (β2‐MG) Methods: The study comprised 120 patients with bipolar disorder of which 90 (30 males and 60 females) have been receiving lithium for 5–38 (mean 16) years, and 30 (10 males and 20 females) have never been exposed to lithium. Results: Lithium‐treated patients, both men and women, showed significantly higher plasma NGAL and urinary β2‐MG and lower urine specific gravity and estimated glomerular filtration rate (eGFR), compared with patients not taking lithium. In these patients, serum NGAL did not correlate with any clinical feature or other parameter of kidney function. Urinary β2‐MG correlated with serum creatinine and eGFR in the whole group of lithium‐treated patients and in addition, in males, with duration of illness, duration of lithium treatment, and urine specific gravity. Conclusions: Lithium treatment causes an impairment of kidney function reflected also by abnormal levels of novel markers of kidney injury. Of these, urinary β2‐MG, as a marker of tubular function seems to be better predictor than serum NGAL in lithium‐treated patients because it shows multiple clinical and biochemical correlations, especially in men. Copyright © 2013 John Wiley & Sons, Ltd.